Impacts of Embedded Generation on Distribution Network Behavior - Puladasu Sudhakar; Sushama Malaji; B. Sarvesh (Institute of Advanced Engineering and Science, 2018)
This paper explores the impacts of multiple embedded generators penetration on distribution system behavior. For this rationale, a IEEE-13 bus distribution feeder was modeled and investigates by assimilating different types of embedded generation (EG) sources. Different scenarios were implemented in which WIND, SOFC FUEL CELL, SOLAR and MICRO TURBINE plants were modeled with high variability of load and generation to observe their impacts on system’s protection, unsymmetrical faults also consider observing impacts effectively. To eradicate the impacts on distribution system with presence of EG’s and distribution system undergone in the event of faults, in this paper primarily reverse power due to EG integration is estimated and sensed with reverse power relay, Further two types of Superconducting Fault Current Limiters Passive resonance CB (PRCB) SFCL and Inverse current injection CB (I-CB are proposed and results are compared for amended solution in mitigating fault current magnitude and over voltages, Finally penetrations levels are computed mathematically and All the modeling and simulations were carried out using MATLAB SIMULINK tool.